Schema Conflict in Laufey’s “Promise”: A Cognitive Stylistic Analysis - Dylan Adji Pratama; Mutiara Balqista Nurazmi; Rahmadsyah Rangkuti (Austronesian: Journal of Language Science & Literature, 2026)
This study explores the profound psychological tension that arises when rational cognitive patterns, such as a firm commitment to distance oneself after a romantic breakup, clash with sudden emotional impulses. This internal friction often disrupts a person’s ability to maintain commitments, leading to a profound struggle between cognitive control and emotional desires. To address this main issue, the objective of this study is to examine Laufey’s song “Promise” to investigate how various forms of figurative language interact with cognitive schemas to construct a complex representation of love characterised by ambiguity and emotional depth. Employing a descriptive qualitative method within the framework of cognitive stylistics, this research found 11 total data points that were divided into metaphor (5 data points), paradox (1 data point), irony (1 data point), hyperbole (3 data points), and repetition (1 data point). The findings reveal that figures of speech function far beyond mere aesthetic ornaments; they act as profound cognitive mechanisms that map the trajectory of the speaker’s psychological struggle. Specifically, metaphors of spatial distance actively establish a rational ‘distance schema’ to create a protective cognitive boundary. However, the subsequent use of hyperboles and paradoxes linguistically manifests the intense cognitive strain and dissonance experienced by the speaker. Ultimately, situational irony acts as the definitive catalyst for schema disruption, brilliantly mirroring the inevitable collapse of cognitive control and the onset of a spontaneous emotional relapse. Through this analysis, the research demonstrates that lyrical choices serve as deliberate cognitive reflections of human vulnerability within modern popular music.